2021
DOI: 10.1007/s40262-021-01077-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Endoxifen for Tamoxifen Precision Dosing: Feasible in Patients with Hormone-Sensitive Breast Cancer

Abstract: Background Endoxifen is the most important active metabolite of tamoxifen. Several retrospective studies have suggested a minimal or threshold endoxifen systemic concentration of 14–16 nM is required for a lower recurrence rate. The aim of this study was to investigate the feasibility of reaching a predefined endoxifen level of ≥ 16 nM (5.97 ng/mL) over time using therapeutic drug monitoring (TDM). Methods This prospective open-label intervention study enrolled patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 59 publications
0
32
2
Order By: Relevance
“…It was assumed that RFS and OS of patients with subtherapeutic endoxifen levels are equal to RFS and OS of patients who were not treated with tamoxifen in the EBCTCG study. This assumption was supported by clinical and pharmacological expert opinion [21].…”
Section: Survival Estimatesmentioning
confidence: 79%
See 2 more Smart Citations
“…It was assumed that RFS and OS of patients with subtherapeutic endoxifen levels are equal to RFS and OS of patients who were not treated with tamoxifen in the EBCTCG study. This assumption was supported by clinical and pharmacological expert opinion [21].…”
Section: Survival Estimatesmentioning
confidence: 79%
“…However, such a trial is probably not feasible since it would require many thousands of patients to participate and a follow-up period of more than a decade [40]. To break out of this potential dead end, physicians are encouraged to implement TDM-a feasible intervention-in the meantime in clinical practice, pending further prospective data [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite tamoxifen dose escalation, only 36% and 79% of these patients reached the threshold, respectively. 27 Moreover, another study in 353 tamoxifen users demonstrated that dose escalation is not feasible for patients with a PM phenotype. 28 These observations stress the need for a solution, other than a dose escalation, to increase endoxifen concentrations in these patients to therapeutic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of TAM involves a series of CYP450 enzymes that convert TAM to its two most active metabolites, END and 4HT, and this process may vary between patients 7 . Because these two metabolites have a 30 to 100 times greater binding affinity for the estrogen receptor than does TAM, and END achieves a 5 to 10 times higher plasma concentration than 4HT, END is thought to be the most active TAM metabolite 18 .…”
Section: Discussionmentioning
confidence: 99%